Rational medical decision making : - Rao, Goutham (McGraw-Hill, 2007)
The book provides a comprehensive overview of many core principles in research design and analysis. It is logically organized, with clear learning objectives at the beginning of each chapter and pertinent examples to illustrate key concepts. The author does a wonderful job of simplifying a subject that has caused much confusion for many medical students and physicians....This is a book that I would enthusiastically recommend to other medical students.